Social roots of inverse nationalism - Antonić, Slobodan (Sociološki pregled, 2025)
Condescension, contempt, hostility, and even hatred towards members of one’s own society – this phenomenon has been observed in many countries. In this paper, it is called inverse nationalism, but other names used in Serbia are also mentioned, with consideration of some local indicators of this phenomenon. The second part of the paper provides an overview of the terms and descriptions of inverse nationalism in other countries (self-hatred, oikophobia, ethnomasochism, Smerdyakovism, Malinchism etc.). The third part of the paper presents some explanations of this phenomenon and indicates that it does not have the same causes in the countries of the centre of the world capitalist system and in the countries of the (semi)periphery. The most useful theoretical explanation for defining inverse nationalism in Serbia is the one given for Malinchism in Mexico: as the internalization of the neo-colonial value system in the function of normalizing neo-imperial domination.